Saturday

April 19, 2014

April 19, 2014

Posted by **Brianna** on Sunday, October 30, 2011 at 11:08pm.

- ****college algebra**** -
**Steve**, Monday, October 31, 2011 at 4:00pmYou want h(h) = h. That is,

3h+4 = h

3(3x+4) + 4 = 3x+4

9x + 12 + 4 = 3x + 4

6x = -12

x = -2

h(-2) = 3(-2) + 4 = -2

Or, using h^{-1}, you could say, recalling that

h^{-1}(h(x)) = x

So, h^{-1}(h(h)) = h^{-1}(h)

h = x

3x+4 = x

2x = -4

x = -2

**Related Questions**

Algebra - (3x+4)/(3x-4)+(3x-4)/(3x+4) --------------------------- Divide top by ...

college algebra - √3x+7=3x+5 How do I solve when the answer is -1?

College Algebra - #2 Choose the end behavior of the graph of the polynomial ...

college algebra - Identify the center and radius of the circles represented by ...

COLLEGE ALGEBRA - SUBTRACTING... 5x^4+3x^2-2x - 5x^4-3x^2+9x _______________ 0x^...

COLLEGE ALGEBRA - SUBTRACTING... 5x^4+3x^2-2x -5x^4-3x^2+9x _______________ 0x^4...

college algebra - y intercept: 3x^2+18x 0=3x^2+18x from here im lost

College Algebra - Divide. (9x^3-10+19+6x^4)/(-2x^2+3x-3) Write your answer in ...

College Algebra - Please help me Divide. (9x^3-10+19+6x^4)/(-2x^2+3x-3) Write ...

college algebra - i need some help with this pleez! f(x+6) f(x)=3x^2-5x+3 if u ...